Symmetrical Periorbital Yellow Plaques in a Patient with Haematological Dyscrasia: A Quiz - Emanuele Cozzani; Andrea Muracchioli; Giulio Fraternali Orcioni; Aurora Parodi (Medical Journals Sweden, 2021)
Abstract is missing (Quiz)